On Stock Market Returns and Returns on Investment - RESTOY, FERNANDO; ROCKINGER, G. MICHAEL (Journal of Finance, 1994)
ABSTRACT This article presents general conditions under which it is possible to obtain asset pricing relations from the intertemporal optimal investment decision of the firm. Under the assumption of linear homogeneous production and adjustment cost functions (the Hayashi (1982) conditions), it is possible to establish, state by state, the equality between the return on investment and the market return of the financial claims issued by the firm. This result proves to be, in essence, robust to the consideration of very general constraints on investment and the inclusion of taxes.